ANALISIS HUBUNGAN KAUSALITAS ANTARA INVESTASI PEMERINTAH DENGAN PERTUMBUHAN EKONOMI KOTA PALEMBANG - Hari Apriansyah; Fachrizal Bachri (Jurnal Ekonomi Pembangunan, 2006)
The main objective of this research is to analyze the causality relationship between government investment and economic growth in Palembang during the  city period of 1994-2005. The data used in this study are secondary data.  To analyse the data, Granger Causality Test which was formulated in a simple regression equation used.  The research result shows that  two  directions causality relationship between government investment and economic growth during  that period. It can be seen from the coefficients result of two regressions which  are not zero (bj â‰  0 and dj â‰  0) and the F statistic tests  are bigger than the F table  (20,799 > 6,26 and 10,788 > 6,26). Keywords : Government investment, Economic growth, Granger Causality.